Comparison of in vitro biocompatibility of silicone and polymethyl methacrylate during the curing phase of polymerization. Issue 7 (26th February 2018) - Song, Wei; Seta, Joseph; Eichler, Michael K.; Arts, Jacobus J.; Boszczyk, Bronek M.; Markel, David C.; Gasbarrini, Alessandro; Ren, Weiping
Abstract: Adverse events have been reported with acrylic bone cements. However, current test standards for acrylic materials fail to characterize the potentially harmful monomers released during the curing stage. In clinical applications, materials are implanted into the human body during this phase. Silicone may be a safer alternative to acrylic cements. Silicone is used in medical applications for its biocompatibility and stability characteristics. Previously, no study has been completed which compares silicone to acrylic cements. In this study, both materials were injected into the cell medium during the curing process which more accurately reflects clinical use of material. Initially, cell cultures followed ASTM standard F813‐07 which fails to capture the effects of monomer released during curing. Subsequently, a modified cell culture method was employed which evaluated cytotoxicity while the materials cured. The objective of this study was to capture toxicity data during curing phase. Thus, the test method employed measured and excluded the impact of the exothermic reaction temperature of polymethyl methacrylate (PMMA) on cell growth. The concentration of PMMA monomer was measured at 1 and 24 h after injecting PMMA into culture plates in a manner consistent with established cell growth methodologies. Our results indicate current in vitro cytotoxicity assays recommended by ASTM standards are unable to reveal the real cytotoxic effect caused by methyl methacrylate monomers during polymerization. Our modified experiment can more accurately illustrate the true nature of the toxicity of materials and improve assay results. In these tests, silicone based elastomeric polymers showed excellent cytocompatibility. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2693–2699, 2018.